2018
DOI: 10.26515/rzsi/v118/i1/2018/121626
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Butterfly Diversity (Lepidoptera: Papilionoidea) from Punjab Agricultural University Campus, Ludhiana, Punjab, India

Abstract: Thirty-three species referable to twenty-four genera belonging to five families, namely, Hesperiidae (1), Lycaenidae (6), Nymphalidae (14), Papilionidae (3) and Pieridae (9) from different localities of University campus were collected and identified. The details on their synonymy, material examined, and host distribution along with plants are provided. The photographs of the adults are also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Out of the 19 species of the family Riodinidae, the species, Abisara bifasciata is the only species which is known to occur in Peninsular India while the other species occur in North and Northeast India. [7,1,9,15,6] . Hence the family Riodinidae and the species, Abisara bifasciata is recorded for the first time from the state Punjab.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 19 species of the family Riodinidae, the species, Abisara bifasciata is the only species which is known to occur in Peninsular India while the other species occur in North and Northeast India. [7,1,9,15,6] . Hence the family Riodinidae and the species, Abisara bifasciata is recorded for the first time from the state Punjab.…”
Section: Resultsmentioning
confidence: 99%
“…The observed richness of butterfly fauna is comparable with reports of earlier studies carried out on the campuses of educational institutions in some adjoining eco-regions. For instance, Pathania et al (2018) reported 33 species of butterflies belonging to 24 genera and five families from Punjab Agricultural University Campus, Ludhiana, Punjab. Singh et al (2016) recorded a total of 23 butterfly species belonging to five families and 18 genera from Khalsa College Amritsar, Punjab.…”
Section: Discussionmentioning
confidence: 99%
“…81 species of 60 genera of butterflies were reported by Singh et al (2016) [14] from district Hoshiarpur, Punjab. Pathania et al (2018) [5] while studying the butterflies' diversity of Punjab Agricultural University campus, Ludhiana recorded 33 species under 24 genera of 5 families. Sharma and Goswami (2021) [11] have recently compiled a list of 134 species found in the state of Punjab.…”
Section: Introductionmentioning
confidence: 99%